An instrumental study of oral vowels in the Kedah variety of Acehnese - Yusuf, Y.Q.; Pillai, S. (Elsevier, 2016)
The variety of Acehnese spoken in Malaysia, in particular the way in which it is pronounced, has thus far received little attention in the literature. One group of Malaysian Acehnese speakers can be found in a village in the northwest of Peninsular Malaysia. The present paper examines the oral monophthong vowels of the Acehnese variety spoken in this village based on an analysis of the formant values of the monophthong vowels produced by speakers from this location. The main aim of the paper is to determine the characteristics of monophthong vowels in the Malaysian Acehnese variety. The first and second formant values of the vowels were extracted and analysed from ten female Malaysians of Acehnese descent living in Kampung Aceh in Kedah. Comparisons with vowels in the Indonesian Acehnese variety were also carried out. Our findings indicate that most of the Malaysian Acehnese monophthongs displayed similar qualities with the Indonesian variety of Acehnese. However, there appears to be a loss of /ʌ/, and a more back production of /ǝ/, and in some cases /a/.